English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Please show the steps and all that


X - Y = -5

X + Y = -3

2007-01-01 11:21:02 · 4 answers · asked by NoNome 2 in Science & Mathematics Mathematics

4 answers

x-y=-5
x+y=-3
======
2x=-8
x=-4

-4+y=-3
y=1

The solution set is (-4,1)

Check:
-4-1=-5
-5=-5

-4+1=-3
-3=-3

2007-01-01 12:44:50 · answer #1 · answered by Anonymous · 4 0

x-y= -5------->equation 1
x+y=-3--------> equation 2
this is a simultaneous equation.
i'm going to use elimination method to find the value of Y first.
(equation 1)-(equation 2)
(x-x)=0
(-y-y)= -2y
(-5-(-3))= -2
-2y= -2,hence, y= 1
plug "y"=1 into any of the equations.i'm gon use equation 1
x-y=-5
x-1=-5
by grouping like terms:numbers to one side and variables to one side.
x=-5+1
therefore,x= -4
to prove that the results is correct,plug in the answers you had for the variables.
y=1;x=-4
equation 1, x-y= -5
-4-1=-5
equation 2,x+y= -3
-4+1= -3
Hence, x= -4;y=1 is correct.

2007-01-01 19:34:53 · answer #2 · answered by Phy A 5 · 3 0

Adding the two equations together 2x = -8 which means x=-4.
Substituting back in for x, y = 1 so the solution is (-4,1)

2007-01-01 19:24:18 · answer #3 · answered by MollyMAM 6 · 3 0

make the first equation into x=
so
x=y-5
substitute into the second equation
y-5+y=-3
2y-5=-3
2y=2
y=1
substitute that into the first equation
x-1=-5
x=-4
check that in the second equation.
-4+1=-3
-3=-3
it works.

2007-01-01 19:31:11 · answer #4 · answered by adriantheace 4 · 3 0

fedest.com, questions and answers